Efficacy of selected adjuvants for protecting Spodoptera litura nucleopolyhedrovirus from sunlight inactivation - Sajap, Ahmad Said; Abdul Bakir, Mohammad; Abdul Kadir, Hussan; Abdul Samad, Norani (2009)
Efficacy of selected adjuvants for protecting Spodoptera litura nucleopolyhedrovirus (SpltNPV) from sunlight inactivation was tested in direct sunlight exposure bioassays and in the field on virus-treated Brassica chinensis var parachinensis plants. All adjuvants, except palm oil, gave significant protection to the virus after 16 h of sunlight exposure, as shown by the larval mortalities. Cumulative mortalities after 14 days show that the virus + Tinopal treatment and the virus not to sunlight treatment attained 100% mortality, while the virus in riboflavin treatment and the crude brown sugar treatment caused mortality of less than 30%. However, the LT50 value of virus + Tinopal was 1.2 times lower than the unexposed virus. All virus-treated plants in the field trials had higher yields and lower damage indices than the control plants. Unlike the results from direct sunlight exposure bioassays, adjuvants, including virus + Tinopal LPW, did not significantly enhance efficacy of the virus against early instars of S. litura in the field. The unformulated virus was as effective as virus + Tinopal LPW and Nurelle-D in protecting the plants from infestation. Thus, in a well-planned pest management program, SpltNPV, without any adjuvant, can be used effectively for controlling S. litura on B. chinensis var parachinensis.